КОНВЕЙЕР ТАСМАЛАРИНИНГ ЧИДАМЛИЛИГИНИ ЯНГИ УСУЛЛАРНИ ҚЎЛЛАШ АСОСИДА ОШИРИШ - Атакулов, Лазизжон; Полвонов, Нурбек; Каюмов, Умиджон (Innovatsion texnologiyalar, 2022)
This article presents the methods of connecting conveyor belts used in mining enterprises, developed new methods for connecting conveyor belts. In addition, the disadvantages of the current connection method are also mentioned. The methodology for conducting experimental studies using newly developed methods and the preliminary results obtained are also presented.